2003
DOI: 10.1007/s00122-003-1352-7
|View full text |Cite
|
Sign up to set email alerts
|

Testing for linkage disequilibrium in the New Zealand radiata pine breeding population

Abstract: Linkage analysis is commonly used to find marker-trait associations within the full-sib families of forest tree and other species. Study of marker-trait associations at the population level is termed linkage-disequilibrium (LD) mapping. A female-tester design comprising 200 full-sib families generated by crossing 40 pollen parents with five female parents was used to assess the relationship between the marker-allele frequency classes obtained from parental genotypes at SSR marker loci and the full-sib family p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In another study conducted in radiata pine, 200 full sib families were used to study the marker-trait associations. In this study, the parental genotypes were also considered during analyses (Kumar et al, 2004), so that the method can be compared with TDT in humans.…”
Section: Marker-trait Association and Mas In Plantsmentioning
confidence: 99%
“…In another study conducted in radiata pine, 200 full sib families were used to study the marker-trait associations. In this study, the parental genotypes were also considered during analyses (Kumar et al, 2004), so that the method can be compared with TDT in humans.…”
Section: Marker-trait Association and Mas In Plantsmentioning
confidence: 99%
“…DNA markers can be applied to achieve earlier selection and more cost-effective selection or to increase selection intensity in forest breeding programmes (Wilcox et al 2007). Simple sequence repeat (SSR) markers were found to be associated with branch cluster frequency and stem straightness in radiata pine (Kumar et al 2004). Association studies for branch cluster frequency and stem straightness have been reported in other species as well (Arcade et al 1996;Cumbie 2010;Lepoittevin et al 2012;Xiong 2010).…”
Section: Communicated By J Beaulieumentioning
confidence: 96%
“…In both orchards, significance was found between loci EMBRA681xEMBRA2 and EMBRA204xEMBRA210. The imbalance may be affected by selection, recombination, migration, population reduction, genetic drift, and population structure (Kumar et al, 2004). Tarazi et al (2010) found genotypic disequilibrium between pairwise loci in open-pollinated seeds of Copaifera langsdorffii, probably due to the inheritance of maternal alleles.…”
Section: Discussionmentioning
confidence: 99%